Blood Coagulation after Long Distance Running: Antithrombin III Prevents Fibrin Formation - Bärtsch, Peter; Haeberli, André; Werner Straub, P (Thrombosis and Haemostasis, 1990)
Physical exercise causes shortening of activated partial thromboplastin time (aPTT) and euglobulin clot lysis time. To investigate whether this activation of coagulation and fibrinolysis leads to in vivo thrombin or plasmin action after long distance running, 19 well trained male runners (36-65 years) were examined 5 to 53 min after termination of a 100 km race and 5 days later after at least 1 day without physical exercise. Compared to the control examination aPTT was decreased (30.2 ± 2.8 vs 35.3 ± 3.0 sec) and the following parameters were increased after the race: betathromboglobulin (40 ± 16 vs 23 ± 7 ng/ml), thrombin-antithrombin III (TAT) complexes (5.5 ± 3.4 vs 2.3 ± 0.7 pg/1), the fibrin(ogen) degradation products fragment E (57 ± 15 vs 35 ± 7 ng/ml) and B(3 15-42 (8.5 ± 2.5 vs 6.5 ± 2.5 ng/ml) (all p values <0.001). Platelet count, platelet factor 4, fibrinoepetide A (FPA) and haematocrit did not change significantly. Increased TAT complexes and unchanged FPA suggest that the generated thrombin was fully inactivated by antithrombin III (AT III) and did therefore not give rise to fibrin formation. The small increase of fibrin(ogen) degradation products indicates a minor in vivo activity of the fibrinolytic system. This investigation demonstrates the importance of AT III in the regulation of haemostasis in activated blood coagulation.